Cornel Iridoid Glycoside Protects Against STAT1-Dependent Synapse and Memory Deficits by Increasing N-Methyl-D-aspartate Receptor Expression in a Tau Transgenic Mice - Ma, Denglei; Huang, Rui; Guo, Kaiwen; Zhao, Zirun; Wei, Weipeng; Gu, Lihong; Li, Lin; Zhang, Lan (Frontiers in Aging Neuroscience, 2021)
P301S transgenic mice are an animal model of tauopathy and Alzheimer’s disease (AD), exhibiting tau pathology and synaptic dysfunction. Cornel iridoid glycoside (CIG) is an active ingredient extracted from Cornus officinalis, a traditional Chinese herb. In the present study, the purpose was to investigate the effects and mechanisms of CIG on tau pathology and synaptic dysfunction using P301S transgenic mice. The results showed that intragastric administration of CIG for 3.5 months improved cognitive impairments and the survival rate of P301S mice. Electrophysiological recordings and transmission electron microscopy study showed that CIG improved synaptic plasticity and increased the ultrastructure and number of synapse. Moreover, CIG increased the expression levels of N-methyl-D-aspartate receptors (NMDAR) subunits GluN1, GluN2A, and GluN2B, and α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluA1. We inferred that the major mechanism of CIG involving in the regulation of synaptic dysfunctions was inhibiting the activation of Janus kinase-2 (JAK2)/signal transducer and activator of transcription 1 (STAT1) signaling pathway and alleviating STAT1-induced suppression of NMDAR expressions. Based on our findings, we thought CIG might be a promising candidate for the therapy of tauopathy such as AD.